THE IMPORTANCE OF THE NEGATIVE ASSOCIATIVE PRIMING CO-OCURRENCE - Rodríguez Santos, José Miguel; Calleja Reina, Marina (Anales de Psicología / Annals of Psychology, 2003)
The growing literature about negative priming (NP) has emphatized the existence of a semantic negative priming (defined as the NP effect when two words belong to the same semantic category or when they have a subordinate o supraordinate relationship). In fact, when NP was defined by Tipper in 1985 he analized the semantic modality. At the moment, we have not found any evidence for associtative NP for pairs of words. Many explanations can be done. Firstly, it is possible that this kind of stimulus (pairs of words with merely associative relationship) do not show any impact in NP due to its own nature. In the other hand, also it is possible that other strategic factors may be necessary to produce such phenomenon, or, that the associative relationship can be weaker than the semantic relationship. So it is necessary increase its associative relationship in order to produce NP. If we were in the correct way, we would have found strong evidence for memory factors in NP. Data collected in this article pointed out to this way. In fact, we have found NP with pairs of words with associtive relationship, when the link between them has been increased by the enlargement of co-ocurrence.